SPATIAL, SEASONAL, AND TEMPORAL VARIATIONS IN RAINFALL AGGRESSIVENESS IN THE SOUTH OF BRAZIL - Álvaro J. Back; Fabiane N. Gonçalves; Fernando M. Fan (Engenharia Agrícola, 2019)
ABSTRACT The objective of this study is to evaluate spatial and temporal variations in rainfall aggressiveness in southern Brazil. A total of 181 rain gauge stations located in southern Brazil with rainfall time series from 1976 to 2015 were used. Seasonal and annual rainfall aggressiveness values measured according to the Modified Fournier Index (MFI) were analyzed. The trends in the data series were evaluated using the Mann-Kendall test at a level of significance of 5%. Maps on spatial and seasonal variations in rainfall aggressiveness were prepared. The percentage of rain gauge stations with significant decreasing trends, significant increasing trends, and no significant trends in rainfall aggressiveness between years was 3.3%, 7.7%, and 89.0%, respectively. Moreover, 90% of stations had no significant trends between seasons. There were seasonal differences in rainfall aggressiveness between the three southern states in Brazil caused by rainfall factors. Rainfall aggressiveness was comparatively higher in the west of Santa Catarina and southwest of Paraná due to the rains originating from the mesoscale convective systems predominant in autumn, and in the north coast of Santa Catarina and east coast of Paraná due to convective and orographic precipitations predominant in the summer.